2016
DOI: 10.1126/science.aad3503
|View full text |Cite
|
Sign up to set email alerts
|

Population-level analysis of gut microbiome variation

Abstract: Fecal microbiome variation in the average, healthy population has remained under-investigated. Here, we analyzed two independent, extensively phenotyped cohorts: the Belgian Flemish Gut Flora Project (FGFP; discovery cohort; N = 1106) and the Dutch LifeLines-DEEP study (LLDeep; replication; N = 1135). Integration with global data sets (N combined = 3948) revealed a 14-genera core microbiota, but the 664 identified genera still underexplore total gut diversity. Sixty-nine clinical and questionnaire-based covari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

138
1,633
10
31

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 1,889 publications
(1,812 citation statements)
references
References 54 publications
138
1,633
10
31
Order By: Relevance
“…In agreement with our predictions (Fig. 5), recent epidemiological studies have shown that BSS is the major explanatory variable for microbiota composition in healthy humans (43,44): Higher BSS scores (less colonic water uptake) correspond to a higher relative abundance of Bacteroidetes.…”
Section: Significancesupporting
confidence: 80%
See 2 more Smart Citations
“…In agreement with our predictions (Fig. 5), recent epidemiological studies have shown that BSS is the major explanatory variable for microbiota composition in healthy humans (43,44): Higher BSS scores (less colonic water uptake) correspond to a higher relative abundance of Bacteroidetes.…”
Section: Significancesupporting
confidence: 80%
“…6, Inset). Furthermore, microbiome sequencing has confirmed nutrient inflow, transit time, and water content to be crucial determinants of microbiota composition (31,32,45,46), with stool consistency (BSS) identified as the single most important factor explaining microbiota variation in a large-scale epidemiological study (44). Our results offer a minimal explanation for these variations: Nutrient inflow and stool consistency affect microbiota composition via changes in luminal pH.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Recent studies employing these technologies have uncovered evidence for both environmental and host genetic association with the microbiome composition [8,11,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. However, to date there is no consensus regarding how and to what extent does host genetics shapes the gut microbiome, as compared to environmental factors.…”
Section: Introductionmentioning
confidence: 95%
“…First, there is an excessive bacterial similarity among individuals sharing a household, but no such similarity was observed across family members without a history of household sharing [8,20,22,35]. Second, over 20% of gut microbiome β-diversity variance can be inferred via several measured environmental factors, such as answers to food frequency and drug use questionnaires [8,33,34], whereas no statistically significant result was obtained when applying a similar methodology to genetic variants [8]. These results further demonstrate that the gut microbiome is predominantly shaped by environmental factors.…”
Section: The Microbiome Is Predominantly Shaped By Non-genetic Factorsmentioning
confidence: 99%